Pembuatan Edible Film Pati Singkong-Kitosan Dengan Penambahan Plasticizer Gliserol Sebagai Plastik Kemasan - Amalia, Zayyana; Zaimahwati, Zaimahwati; Zuhra, Zuhra (Jurnal Riset, Inovasi, Teknologi & Terapan, 2022)
Packaging of food products using edible films plays an important role in protecting foodstuffs from microbial contamination and improving the quality of foodstuffs during storage. The addition of chitosan as an antibacterial with the aim of inhibiting pathogenic microbes that cause food contamination. This study aims to study the effect of increasing the volume of chitosan and glycerol on the characteristics of edible films. In this study, an edible film made from cassava starch-chitosan was made with various compositions of 5:5, 6:4, 7:3, 8:2 and 10:0 using the plasticizer glycerol 1; 1,2; 1.5; 1.7; and 2 ml. Furthermore, the characterization of the edible film was carried out including thickness test, water resistance test, ALT microbial test, FTIR test, and application to carrots to determine the shelf life. Edible film with a composition of 5:5 with a glycerol volume of 1 ml showed the best results, which had a thickness of 0.095 mm, water resistance 60.91%, and the number of colonies was 215 cfu/ml. In the application of edible film, carrots have a shelf life of 5 days, carrots coated with edible film still have good physique. Meanwhile, carrots that are not coated with edible film have fungal growth.